Reviving the Ganges water machine: potential - Amarasinghe, Upali A. (Copernicus GmbH, 2016)
The Ganges River basin faces severe water challenges related to a mismatch between supply and demand. Although the basin has abundant surface water and groundwater resources, the seasonal monsoon causes a mismatch between supply and demand as well as flooding. Water availability and flood potential is high during the 3–4 months (June–September) of the monsoon season. Yet, the highest demands occur during the 8–9 months (October–May) of the non-monsoon period. Addressing this mismatch, which is likely to increase with increasing demand, requires substantial additional storage for both flood reduction and improvements in water supply. Due to hydrogeological, environmental, and social constraints, expansion of surface storage in the Ganges River basin is problematic. A range of interventions that focus more on the use of subsurface storage (SSS), and on the acceleration of surface–subsurface water exchange, has long been known as the Ganges Water Machine (GWM). The approach of the GWM for providing such SSS is through additional pumping and depleting of the groundwater resources prior to the onset of the monsoon season and recharging the SSS through monsoon surface runoff. An important condition for creating such SSS is the degree of unmet water demand. The paper shows that the potential unmet water demand ranging from 59 to 124 Bm3 year-1 exists under two different irrigation water use scenarios: (i) to increase irrigation in the Rabi (November–March) and hot weather (April–May) seasons in India, and the Aman (July–November) and Boro (December–May) seasons in Bangladesh, to the entire irrigable area, and (ii) to provide irrigation to Rabi and the hot weather season in India and the Aman and Boro seasons in Bangladesh to the entire cropped area. However, the potential for realizing the unmet irrigation demand is high only in 7 sub-basins in the northern and eastern parts, is moderate to low in 11 sub-basins in the middle, and has little or no potential in 4 sub-basins in the western part of the Ganges basin. Overall, a revived GWM plan has the potential to meet 45–84 Bm3year-1 of unmet water demand.